Implementasi Gerakan Sedekah Rosok (GSR) dalam Pemberdayaan Ekonomi dan Kepedulian Lingkungan: Studi pada LAZISNU Ranting Karanganyar dan Pagu, Kecamatan Wates - Aviva Damayanti; Muhammad Taufiqkur Rohman; Rosita Septia Farhah; Zulfi Naufal Nasik; Ririn Tri Puspita Ningrum (MONETARIUM: Journal of Economics Business and Management, 2026)
Community-based waste management has emerged as an alternative approach to addressing environmental problems while improving community welfare. One innovative initiative is the Waste Alms Movement (Gerakan Sedekah Rosok/GSR), which integrates waste management with Islamic philanthropic values. This study aims to analyze the implementation of the Waste Alms Movement in promoting economic empowerment and environmental awareness at LAZISNU Karanganyar and Pagu Branches, Wates District, Kediri Regency. This research employed a qualitative approach using a multi-site case study design. Data were collected through observation, in-depth interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña through within-case and cross-case analyses. The findings reveal that both branches successfully implemented GSR by collecting recyclable waste and selling it to finance educational, health, social, religious, and community empowerment programs. Differences in implementation strategies were influenced by organizational characteristics, human resources, and service coverage; however, both branches succeeded in increasing community participation, strengthening environmental awareness in waste management, and improving community welfare. Furthermore, GSR expands the practice of Islamic philanthropy by utilizing recyclable waste as an inclusive form of charity, making it an innovative and sustainable model for economic empowerment and environmental conservation.